Markers of gastrointestinal diseases - V. L. Ostanko; T. P. Kalacheva; K. A. Kulumaeva; N. A. Li; E. V. Beloborodova; I. L. Purlik; E. V. Kalyuzhina; N. G. Brazovskaya; V. V. Kalyuzhin (Бюллетень сибирской медицины)
The lifestyle of people nowadays and poor diet are factors affecting the increasing incidence of digestive diseases in people all over the world. The search for new methods of early diagnosis of the disease is an urgent issue of modern medicine. In the last decade, much attention has been paid to various biological markers that can be used to assess the risk of disease development, the response to therapy, and the possible development of complications. Biomarkers in clinical medicine can be used as additional tools not only to improve early diagnosis of gastrointestinal diseases but also to assess the effectiveness of therapy.The aim of this lecture was to analyze and systematize biomarkers in various gastrointestinal diseases.